2019 IEEE 18th International Symposium on Network Computing and Applications (NCA) 2019
DOI: 10.1109/nca.2019.8935060
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized UAV-based Supervision and Connectivity: Challenges and Opportunities

Abstract: The use of drones has become more widespread in recent years. Many use cases have developed involving these autonomous vehicles, ranging from simple delivery of packages to complex emergency situations following catastrophic events. The miniaturization and very low cost of these machines make it possible today to create large meshes to ensure network coverage in disaster areas, for instance. However, the problems of scaling up and self-organization are necessary to solve problems in these use cases. This posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The authors concluded their work with the challenges in both DL and UAV autonomy. The short review paper in [36] tried to reiterate the importance of self-organization (for a detailed discussion on self-organization in cellular networks, the readers are referred to [37]) in UAV-assisted connectivity. The scalability issue in UAV-assisted networking was raised, and the role of distributed algorithms in mitigating such issues was also discussed.…”
Section: Related Workmentioning
confidence: 99%
“…The authors concluded their work with the challenges in both DL and UAV autonomy. The short review paper in [36] tried to reiterate the importance of self-organization (for a detailed discussion on self-organization in cellular networks, the readers are referred to [37]) in UAV-assisted connectivity. The scalability issue in UAV-assisted networking was raised, and the role of distributed algorithms in mitigating such issues was also discussed.…”
Section: Related Workmentioning
confidence: 99%
“…A great number of recent works have been published in this field in the research literature [ 8 , 9 ]. In [ 10 ], the authors highlight the challenges in terms of connectivity in self-organized UAV deployments involving many UAVs. Attending to the contribution of the paper in the area of sensor interconnection using UAVs, in the following we focus on the application of these vehicles in IoT scenarios [ 11 ].…”
Section: Related Workmentioning
confidence: 99%
“…[8]. Flying Ad-hoc Networks (FANET) [1] can fill the lack of networking infrastructure by allowing the aerial devices to cooperate efficiently to collect data from observations or communications with ground sensors, and gather information to a central processing unit [2,14].…”
Section: Introductionmentioning
confidence: 99%